The Obligation to Ensure the Conformity of International Treaties with the Constitution - Juwana, Hikmahanto (Indonesian Journal of International Law, 2011)
Ever since its Independence, Indonesia has acceded to numerous international treaties. Indonesia’s accessions to international treaties are done by signature, and there are treaties which undergo a ratification process legalised by a Law (Undang-undang) or a Presidential Regulation (Peraturan Presiden). This article will review the various aspects related to the need of ensuring the conformity of international treaties with Indonesia’s 1945 Consitution. Firstly, this paper will discuss why the conformity of international treaties acceded by Indonesia with Indonesia’s 1945 Constitution needs to be ensured. Discussed next is Indonesia’s practice in acceding to international treaties. Then, the paper will consider the possibility of instruments of ratifications both in the form of Law and Presidential Regulation being judicially reviewed by the Constitutional Court or the Supreme Court and its implications. Lastly, this paper will elaborate the steps Indonesia must take in the future. In practice, there are no actual process to ensure the conformity between an international treaty and the Constitution. The government should review every international treaty that would be acceded by Indonesia so that its conformity with the Constitution is ensured.